Картографічна модель оцінки забруднення земель вздовж автомобільних доріг - Кліменко, В.І. (Екологічна безпека та природокористування, 2012)
The technology of decoding of areas of pollution of lands along auto routes which allows to analyse in short terms a real condition of forest shelter belts of any region of Ukraine, as a factor of protection of lands from pollution by emissions of motor transport or for ensuring effective land use is offered.